Climate change hazards, physical infrastructure systems, and public health pathways - Maria Ikonomova; Kristen MacAskill (Environmental Research: Infrastructure and Sustainability, 2023)
Climate-related hazards such as heatwaves, flooding, wildfires, and storms will increase morbidity and mortality unless infrastructure decision-makers—including urban planners, infrastructure asset managers, and utility providers—implement preventive measures to protect public health from these hazards. Existing research and policies have not systematically identified the key risk factors that these decision-makers need to manage to protect public health in a changing climate. This gap leads to unclarity regarding what infrastructure interventions are required to prevent climate-related health risks and what actors have a responsibility to manage these risks. The Climate-Health-Infrastructure-Pathways Model is introduced in this paper to address this gap and provide a conceptual map that captures the role of physical infrastructure systems in the pathways between climate-related hazards and health risks. The model surpasses what can be found in existing climate change research and policy, including the latest IPCC reporting, and is a conceptual qualitative tool that offers a typology of climate and health risks for infrastructure management. Decision-makers can use the model as a starting point to review the coverage of their current climate risk management plans and identify further opportunities to develop preventive infrastructure responses to protect public health in a changing climate.